2023
DOI: 10.1108/ils-04-2023-0035
|View full text |Cite
|
Sign up to set email alerts
|

The beginning of ChatGPT – a systematic and bibliometric review of the literature

Hasnan Baber,
Kiran Nair,
Ruchi Gupta
et al.

Abstract: Purpose This paper aims to present a systematic literature review and bibliometric analysis of research papers published on chat generative pre-trained transformer (ChatGPT), an OpenAI-developed large-scale generative language model. The study’s objective is to provide a comprehensive assessment of the present status of research on ChatGPT and identify current trends and themes in the literature. Design/methodology/approach A total of 328 research article data was extracted from Scopus for bibliometric analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
3
4
0
Order By: Relevance
“…Keywords such as "human", "question", "answer", "ai" may indicate researchers' interest in the theme of relationships between humans and AI, as well as the methods by which people utilise technology based on artificial intelligence. These patterns are consistent with global trends indicating a leading role for the United States in artificial intelligence research, as confirmed by research by other authors [11,12]. Moreover, the emergence of new research clusters in various databases indicates evolving interests and potential new research directions, especially in natural language processing and its applications in various sectors, including healthcare and education.…”
Section: Abstract and Co-occurrence Of Abstractsupporting
confidence: 88%
See 2 more Smart Citations
“…Keywords such as "human", "question", "answer", "ai" may indicate researchers' interest in the theme of relationships between humans and AI, as well as the methods by which people utilise technology based on artificial intelligence. These patterns are consistent with global trends indicating a leading role for the United States in artificial intelligence research, as confirmed by research by other authors [11,12]. Moreover, the emergence of new research clusters in various databases indicates evolving interests and potential new research directions, especially in natural language processing and its applications in various sectors, including healthcare and education.…”
Section: Abstract and Co-occurrence Of Abstractsupporting
confidence: 88%
“…Similar patterns of regional research leadership and collaboration are evident across disciplines, including medical research, with Barrington et al highlighting the dominance of the United States in ChatGPT medical publications [13]. The review by Baber et al further confirms the intense research activity in the United States, while acknowledging the significant contributions of other regions such as China and India [12]. These patterns may indicate a robust AI research infrastructure and a high level of interdisciplinary discourse, fostering progress and a comprehensive approach to the ethical, legal and educational implications of AI technologies such as ChatGPT.…”
Section: Source Of Articlesmentioning
confidence: 78%
See 1 more Smart Citation
“…The release of ChatGPT attracted many researchers' attention, and many researchers were concerned with ChatGPT's use in language education. The review of ChatGPT indicated that the use of ChatGPT is still in its early stage and the learning system was one of the main concerns (Baber et al, 2023). Barrot (2023) discussed the pitfalls and potentials of ChatGPT's use in L2 writing.…”
Section: Literature Review Previous Review and Bibliometric Analysismentioning
confidence: 99%
“…According to the research of Bozkurt et al [9], ChatGPT can accurately and helpfully answer a variety of queries and assist students in completing assignments, including writing essays and scientific papers [10][11][12]. Furthermore, according to the research of Wang and Chen [13], ChatGPT can boost student enthusiasm and activity levels, which could lead to better learning outcomes.…”
Section: Introductionmentioning
confidence: 99%